Faktor-Faktor yang Mempengaruhi Perataan Laba (Income Smoothing) pada Perusahaan Manufaktur yang Terdaftar Di BEI 2016-2020 - Rena Naena Fitriana Putri; Cahyani Nuswandari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
The main thing of the operational activities of a business company is to make a profit. In fact, maximizing profit is the main goal of all business decisions and activities. The company will go bankrupt if it does not make a profit. This study discusses the Factors Affecting Income Smoothing in Manufacturing Companies Listed on the Stock Exchange 2016-2020. Therefore, the purpose of this study is to test and analyze the effect of firm size, financial leverage, profitability, cash holding, and auditor reputation on income smoothing in manufacturing companies listed on the IDX. The method used in this research is a quantitative method with a descriptive approach. The results of this study can be said that company size, profitability, and cash storage have no significant effect on earnings performance. Meanwhile, financial leverage and auditor reputation have a negative and significant effect on earnings management in manufacturing companies.